Robustness of personal initiative in moderating entrepreneurial intentions and actions of disabled students - Dakung Reuel Johnmark; John C. Munene; Waswa Balunywa (Cogent Business & Management, 2016)
Entrepreneurship is vital in the areas of innovation, job creation, nations' economic and societal advancement. In view of that, personal initiative is seen to be important in moderating the relationship between intention and entrepreneurial action. This study focuses on investigating the moderating role of personal initiative on intention and entrepreneurial action relationship of disabled students. The study followed a descriptive survey where quantitative approach was employed. A total number of 250 questionnaires were administered to disabled students across the tertiary institutions (Universities, Polytechnics and colleges) in Plateau State and Abuja-Nigeria. Analysis of data involved the use of statistical package for social sciences (SPSS version 22.0). Hypotheses were tested using structural equation model. Results revealed that pedagogy significantly and positively influences entrepreneurial actions. Also, personal initiative (proactiveness, resilience and innovation) moderates the relationship between intention and entrepreneurial actions of disabled students.
Keywords: 650